Ciri persekitaran hidrologi dan sedimentasi Sungai Telom, Cameron Highlands - Noraini Wahida Abdullah,; Mohd Ekhwan Hj.Toriman, (Journal of Faculty of Social Sciences and Humanities. Universiti Kebangsaan Malaysia, 2011)
River modeling plays a vital role in predicting river respond to any natural and artificial modifications. This study on river modeling was carried out in order to analyse the hidraulic and hidrological characteristic as well as sediment trends of Telom River in Cameron Highlands. In this study, the hidrographic survey was carried out on 28 October 2008 while data on water and sediment sampings was done twice, namely on 28 October 2008 and 8 February 2009, respectively. To model the river, the XPSWMM, a 1-D hydrodynamic sofware was used to simulate the river discharge. Calibration and validation were also carried out to confirm the model developed. The hidraulic simulation, as modeled by XPSWMM show bankfull discharge was recorded in node 7 and link 17 which the estimated values were 1.02 m3/s and 2.40 m3/s, respectively. Besides, sediment analyse was also carried out to evaluate sediment trends of the study area. The result found that sediment estimate entered to Telom River was high about 172,324.56 kg / km²/ year and the types of sediment that entered Telom River are mainly coarsif and grit